ONLINE SPEAKING ASSESSMENT DURING THE COVID PANDEMIC: : Impelementation, Problems, and Strategic Solutions - Tedi Rohadi (English Journal Literacy Utama, 2023)
Assessment is one of the basic elements of the teaching and learning process. With assessment, teachers can measure students' abilities. Teachers can measure the competencies that students achieve during the teaching process. In this pandemic era, the activity of the teaching process does not apply in the classroom. However, the teaching process can be applied online using technology. The objectives of this study are: (1) For the online voice assessment feature; (2) Investigate the implementation of online assessment of speaking skills in vocational schools; (3) Research the gaps and solutions to overcome the gaps in the implementation of online voice assessment in the pandemic era with 21st century skills. This study uses a qualitative model description to investigate the case design. The researcher collects data through interviews. The interview was conducted with an English teacher who teaches grade 12 of one of the SMKN in Kota Cirebon. The results of this study showed that the implementation of online speaking skills assessment is using WhatApp as a means of communication in the learning and assessment process, and speaking tasks are guided by using video dialogues and video presentations. The problems experienced by teachers in carrying out online speaking assessment are students' ability to think critically and responsibility to perform and fulfil the tasks; the limited media used in the online speaking skills assessment which is just WhatsApp, the kind of speaking task that is not compatible with 21st century skills. Then there are solutions to counter those problems are by teachers motivating students, guiding students in critical thinking and last but not least the role of government in developing and introducing how to use online platforms.